MANAGEMENT OF ASRIGDARA THROUGH VIRECHANA KARMA (International Journal of Ayurveda and Pharma Research, 2021)
Dysfunctional uterine bleeding is a state of Abnormal uterine bleeding (AUB) without any clinically detectable organic, systemic & iatrogenic cause (pelvic pathology like tumor, inflammations excluded). DUB represents a particular type of AUB and is defined as excessive, prolonged and irregular bleeding of endometrium with frequency less than 21 days, duration more than seven days that does not cause pain and does not involve any organic lesion. Based on the clinical features it can be compared with Asrigdara mentioned in Ayurvedic classics. Asrigdara is one of the commonly met problems in Gynae OPD among peri menopausal women. One half of women among the AUB will have DUB. 10 – 15% of women experience episodes of DUB at some time during their reproductive age. This study was conducted in a single patient. A lady of age 41 years, having problem of prolonged bleeding since one and half years came to OPD of Prasuti and Stri roga, National Institute of Ayurveda, Jaipur. She had taken hormonal preparations and haemostatics for five continuous months along with D& C done for same problem, after wards bleeding increased even more and then doctors have given hysterectomy advice as the last resort. Patient was posted for Virechan Karma as classical schedule owing to her Agni and Vyayamshakti. Snehapan was done by plain Go Ghrita and Virechan was done by Trivritalehyam. Followed by few oral medicines after Samsarjana Karma. The patient was followed up for three months. There is significant reduction in amount of blood flow along with increased inter – menstrual period. Thus, we can conclude from the study that Ayurveda regimen plays an effective role in management of Asrigdara.